Elucidation of Mechanisms by Which Microplastics (PET) Facilitates the Rapid Growth of Benthic Cyanobacteria and Toxin Production in Aquatic Ecosystems - Rashid Mir; Shrooq Albarqi; Wed Albalawi; Ghaida Alanazi; Shouq S. Alsubaie; Razan I. Alghaban; Hanadi Saud Alanazi; Nora Taleb Alsharif; Manal M. Aljammaz; Nouf Faisal Alghabban; Wafaa Seluman Alhwiti; Alaa Albogmi; et al. (Metabolites, 2025)
Polyethylene terephthalate (PET) is one of the most frequently used synthetic polymers and it plays a major role in plastic pollution in aquatic environments. As PET undergoes environmental degradation, it sheds microplastics and chemical leachates, which have an effect on microbial communities, including benthic cyanobacteria. This review focuses on the molecular processes by which PET microplastics and their associated leachate affect the growth, physiological performance, and ecological performance of benthic cyanobacteria. We explore how PET-derived compounds serve as carbon and energy sources or signaling molecules, possibly affecting photosynthesis, nitrogen fixation, or stress response pathways through changes in gene expression. Moreover, the function of PET leachates as environmental modulators of microbial community structure, generators of reactive oxygen species (ROS), and disruptors of hormonal and quorum sensing networks are also outlined. Knowledge of these interactions is essential for the evaluation of the wider ecological risks resulting from plastic pollution and the likelihood of cyanobacterial blooms in PET-polluted environments. This review synthesizes evidence on how PET microplastics and leachates act as carbon sources and stressors, modulating gene expression to promote benthic cyanobacterial growth and toxin production, potentially exacerbating ecological risks in polluted aquatic systems.